The Effect of Hypnotherapy on Postpartum Pain and Depression in Women with Post Caesarean Delivery - Mahandaru, Araafi Hariza; Respati, Supriyadi Hari; Sulistyowati, Sri; Laqif, Abdurahman; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Postoperative pain is one of the most common problems in women after cesarean section. Caesarean section is also associated with post-partum depression. Hypnotherapy is one of the complementary therapy options that are effective and efficient in reducing pain symptoms and post-partum depression. This study aimed to analyze the effect of hypnotherapy on the level of pain and post-partum depression in post-cesarean section patients.Subjects and Method: This was an experimental single-blind randomized controlled trial with a post-test group design, which was conducted from January to April 2021, at the Dr. Moewardi and Universitas Sebelas Maret Hospitals, Surakarta. A sample of 80 patients with cesarean section was divided into two groups, namely 40 patients in the hypnotherapy group and 40 patients in the control group. The independent variable was hypnotherapy. The dependent variables were pain and depression. Hypnotherapy was carried out by self-hypnosis using audio recordings of hypnotherapy in 2 sessions before and after the cesarean section procedure. The pain was measured by the Numeric Rating Scale. Post-partum depression was measured by the Edinburgh Postnatal Depression Scale. The data were analyzed by an independent t-test.Results: Post-cesarean section pain in the group of hypnotherapy (Mean= 4.58; SD= 1.20) was lower than without hypnotherapy (Mean= 6.48; SD= 1.01), and it was statistically significant (p<0.001). Postpartum de-pression in the group of hypnotherapy (Mean= 6.08; SD= 1.60) was lower than non-hypnotherapy group (Mean= 8.48; SD= 3.78), and it was statistically significant (p <0.001).Conclusion: Hypnotherapy has a significant effect on reducing pain and post-partum depression in post-cesarean section patients.Keywords: Hypnotherapy, pain levels, post-partum depression, post-cesarean sectionCorrespondence: Araafi Hariza Mahandaru. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta, Jl. Kolonel Sutarto, Jebres, Surakarta 57126, Central Java. Email: mahandarurafi@gmail.com.Indonesian Journal of Medicine (2021), 06(02): 194-205https://doi.org/10.26911/theijmed.2021.06.02.08